Industry-science-interaction in innovation: The role of transfer channels and policy support - Paolo Carioli; Dirk Czarnitzki; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We investigate the effects of different channels of industry-science collaboration on new product sales at the firm-level and whether government subsidies for collaboration make a difference. We distinguish four collaboration channels: joint R&D, consulting/contract research, IP licensing, human resource transfer. Employing firm-level panel data from the German Community Innovation Survey and a conditional difference-in-differences methodology, we find a positive effect of industry-science collaboration on product innovation success only for joint R&D, but not for the other three channels. The positive effect is limited to subsidized collaboration. Our results suggest that government subsidies are required to bring firms and public science into forms of collaboration that are effective in producing higher innovation output.
Keywords: O31; O38; 330; Industry-science collaboration; transfer channels; product innovation; treatment effects analysis